2007
DOI: 10.1523/jneurosci.2993-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-Specific Modulation of GABAergic Synaptic Transmission by μ-Opioid Receptor in the Mouse Striatum with Green Fluorescent Protein-Expressing Dopamine Islands

Abstract: The striatum is a heterogeneous mosaic of two neurochemically, developmentally, and functionally distinct compartments: the -opioid receptor (MOR)-enriched striosomes and the matrix. Preferential activation of the striosomes and persistent suppression of the matrix have recently been suggested to represent neural correlates of motor stereotypy. However, little is known concerning the physiological properties of the striosomes. We made patch-clamp recordings from medium spiny neurons in identified MOR-immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 47 publications
7
92
1
Order By: Relevance
“…In fact, presynaptic inhibition of corticostriatal excitatory inputs by MOR activation was demonstrated to be mediated by K + channel modulation in the rat striatum [30]. Likewise, we found that MOR activation inhibited GABA release mainly through activation of 4-AP-sensitive K + channels by suppression of the adenylate cyclase pathway in the striosomes [14]. On the other hand, involvement of the arachidonic acid cascade in the presynaptic modulation of IPSCs by MOR appeared unlikely in the striatum, although it has been reported in the periaqueductal gray and central amygdala [56,57].…”
Section: Presynaptic Inhibition Of Ipscs By μ-Opioids In the Striosomessupporting
confidence: 56%
See 2 more Smart Citations
“…In fact, presynaptic inhibition of corticostriatal excitatory inputs by MOR activation was demonstrated to be mediated by K + channel modulation in the rat striatum [30]. Likewise, we found that MOR activation inhibited GABA release mainly through activation of 4-AP-sensitive K + channels by suppression of the adenylate cyclase pathway in the striosomes [14]. On the other hand, involvement of the arachidonic acid cascade in the presynaptic modulation of IPSCs by MOR appeared unlikely in the striatum, although it has been reported in the periaqueductal gray and central amygdala [56,57].…”
Section: Presynaptic Inhibition Of Ipscs By μ-Opioids In the Striosomessupporting
confidence: 56%
“…3). This MORmediated suppression of GABAergic IPSCs in the strio- [14] somes was proved to be presynaptic. Negative presynaptic modulation of GABAergic inhibitory transmission takes place only in the striosome compartment.…”
Section: Presynaptic Inhibition Of Ipscs By μ-Opioids In the Striosomesmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, this inhibition of GABA receptors induced by tramadol has been shown to be secondary to its opioid receptor agonist activity. In addition, continued pharmacological opioid receptor agonist activity has been proven to precipitate seizures via a GABA inhibitory pathway [6,7]. Therefore, the present study has been designed to pharmacologically investigate the role of opioid and GABA receptors in the seizurogenic effect of tramadol on pentylenetetrazole-treated mice and on seizure-like behavioural symptomatology precipitated per se by tramadol.…”
Section: Tramadol (1rs2rs)-2-[(dimethylamino)-methyl]-1-(3-mentioning
confidence: 99%
“…Inhibition of GABA receptors has been found to potentiate the severity of seizures in animal models [13,14]. In addition, GABA receptor inhibition induced by tramadol can be secondary to its opioid receptor agonist activity [13], and continuing this agonist activity on opioid receptor has been proven to precipitate seizure due to inhibition of GABA pathways [15,16]. In addition to overdose, seizures have been reported in patients receiving tramadol at recommended doses [17].…”
Section: Introductionmentioning
confidence: 99%